"FERAL WITH VULNERABILITY": on the argonauts. Issue 1 (2nd January 2018) - Mitchell, Kaye
Abstract: This brief meditation on Maggie Nelson's The Argonauts reads it as elaborating a politics and ethics of vulnerability in both its thinking and its formal qualities, thereby showing us the radical aesthetic, personal and political potential of this state of apparent unguardedness. I consider, in turn, the text's treatment of emotional vulnerability (being undone by others), physical vulnerability (the pregnable, penetrable, in-transition, mortal body), the vulnerability of gender (its precariousness) and our vulnerability to gender (our need to pass, sometimes), as well as the vulnerabilities of the apparently confessional writer and of the text itself (its radical intertextuality).